1991
DOI: 10.1172/jci115388
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of the endothelial and epithelial barriers of the lung in sheep to Escherichia coli endotoxin.

Abstract: Although intravenous Escherichia coli endotoxin has been used extensively in experimental studies to increase lung endothelial permeability, the effect of E. coli endotoxin on lung epithelial permeability has not been well studied. To examine this issue in sheep, bidirectional movement ofprotein across the lung epithelial barrier was studied by labeling the vascular space with 13"I-albumin and-by instilling 3 ml/kg of an isosmolar protein solution with`-I-albumin into the alveoli. E. coli endotoxin was adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
205
0
7

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(228 citation statements)
references
References 33 publications
16
205
0
7
Order By: Relevance
“…Overall, these findings are in accordance with the findings of WIENER-KORNISH et al [45], who have investigated the effect of E. coli endotoxin on sheep lung epithelium in vivo. These authors demonstrated that despite leading to a marked increase in interstitial pulmonary oedema and the number of neutrophils in the alveolar airspaces, E. coli endotoxin did not alter the alveolar epithelial permeability, as indicated by a lack of bidirectional movement of 125 I-labelled albumin across the alveolar epithelium.…”
Section: Allergen Air Pollutantssupporting
confidence: 93%
“…Overall, these findings are in accordance with the findings of WIENER-KORNISH et al [45], who have investigated the effect of E. coli endotoxin on sheep lung epithelium in vivo. These authors demonstrated that despite leading to a marked increase in interstitial pulmonary oedema and the number of neutrophils in the alveolar airspaces, E. coli endotoxin did not alter the alveolar epithelial permeability, as indicated by a lack of bidirectional movement of 125 I-labelled albumin across the alveolar epithelium.…”
Section: Allergen Air Pollutantssupporting
confidence: 93%
“…The other four guinea pigs remained anesthetized until the 1-h experimental time had passed and were then killed, and samples were obtained. At this time, a blood sample was obtained for FD70 analysis, and the lungs were collected for determination of extravascular plasma equivalents as previously described (31,34,40,46). Trichloroacetic acid (TCA) precipitation of plasma and urine samples verified that the FITC label (Ͼ97%) remained bound to the dextran tracer throughout the experimental time period.…”
Section: Endothelial and Epithelial Protein Permeabilitymentioning
confidence: 99%
“…The significance of lung endothelial injury and increased permeability in ALI is well documented (6). Because an intact alveolar epithelial barrier is necessary to prevent alveolar flooding and facilitate recovery from acute respiratory distress syndrome (ARDS), lung epithelial integrity and function are important determinants of the clinical outcome in ALI (22,26,32). When alveolar type II cells are injured, normal alveolar epithelial fluid transport and removal of alveolar edema fluid are impaired (23).…”
mentioning
confidence: 99%